2008
DOI: 10.1016/j.compscitech.2007.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Study on friction and wear behavior of polyphenylene sulfide composites reinforced by short carbon fibers and sub-micro TiO2 particles

Abstract: Study on friction and wear behavior of polyphenylene sulfide composites reinforced by short carbon fibers and sub-micro TiO particles. Composites Science and Technology, Elsevier, 2009, 68 (3-4) AbstractPolyphenylene sulfide (PPS) composites filled with short carbon fibers (SCFs) (up to 15 vol.%) and sub-micro-scale TiO 2 particles (up to 7 vol.%) were prepared by extrusion and subsequently injection-molding. Based on the results of sliding wear tests, the tribological behavior of these materials was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(78 citation statements)
references
References 27 publications
3
75
0
Order By: Relevance
“…The feasible optimal operating conditions can be determined to fabricate monodispered uniform TiO 2 particles for practical cases. Preparation of composites of polyphenylene sulfide (PPS) filled with short carbon fibers (SCFs) and sub-micron particles of TiO 2 to study the tribological behaviour of the composite using ANNs has been reported by Jiang et al (Jiang et al, 2008). The extrusion and injectionmolding technique to prepare the particles followed by sliding wear tests to optimize the composition of PPS, suggested 15 vol.% SCF and 5 vol.% TiO 2 as the lowest specific wear rate.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The feasible optimal operating conditions can be determined to fabricate monodispered uniform TiO 2 particles for practical cases. Preparation of composites of polyphenylene sulfide (PPS) filled with short carbon fibers (SCFs) and sub-micron particles of TiO 2 to study the tribological behaviour of the composite using ANNs has been reported by Jiang et al (Jiang et al, 2008). The extrusion and injectionmolding technique to prepare the particles followed by sliding wear tests to optimize the composition of PPS, suggested 15 vol.% SCF and 5 vol.% TiO 2 as the lowest specific wear rate.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…PPS's extreme inertness toward organic solvents, and inorganic salts and bases accounts for its outstanding performance as a corrosion-resistant coating suitable for contact with foods [65].…”
Section: Polyphenylene Sulfide Resinsmentioning
confidence: 99%
“…Because, the room temperature is higher than the T g of the polypropylene (around 0°C). Moreover, aromatic thermoplastic polymers, such as polycarbonate [16,17], polybutylene terephthalate [18], polyethersulfone [19][20][21], polyetherimide [19,22,23], polyimide [24,25], polyetheretherketone [19,[26][27][28][29] and polyphenylenesulfide [30][31][32] have also been studied for high performance carbon fibers (CFs)/polymer matrix composites. In general, the aromatic polymers have high temperature resistance, high modulus of elasticity, and water resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interfacial structure and the improved adhesion between the matrix polymers and carbon fibers should be important to realize the high potential of the composites. Polybutylene terephthalate [18], polyetheretherketone [19,[26][27][28][29][30] and polyphenylenesulfide [31][32][33] are semi-crystalline thermoplastic polymer matrices. The crystal size, the crystal structure, and the crystallinity would be influenced by the surface of carbon fibers as crystalization-nucleus, as well as by the cooling rate and the annealing in the fabrication process.…”
Section: Introductionmentioning
confidence: 99%